Estudio de Adaptación de Siete Pastos y Tres Mezclas Forrajeras con la utilización de Lactofermentos en el Barrio San Luis de Yacupungo Parroquia Pastocalle Cantón Latacunga Provincia de Cotopaxi, 2018 – 2019. - Reino Araujo, Aldo Martin (2019)
The present investigation was carried out in the San Luis de Yacupungo Community, located in Pastocalle Parish, Latacunga Canton, Cotopaxi Province, with the following Latitude coordinates: 07669966 and longitude 9923785 at a height 3250 meters above sea level, the objective was to determine the pasture of Better adaptability to the sector. As treatments, seven different pastures and three forage mixtures were used, with the application of an enriched lactoferment obtaining twenty treatments, the experimental design implemented was in divided plots (A x B) with three repetitions, where the following variables were analyzed: plant height , coverage and bromatological analysis of the grass. Obtaining the following results: the grass with the highest height is t4 ryegrass, with an average of 14.32 and 25.95 at 43 and 50 days respectively. The grass with the highest percentage of protein was T2 Red Clover with an average of 20.59%, the best percentage of raw fiber was T4 Ryegrass with an average of 27.16% and the one with the highest percentage of fats was for the T9 Vicia mix -Ovenna with an average of 2.27%. Regarding the ELN, it is observed that the best percentage is T4 ryegrass with an average of 47.70%. The costs per Ha are: $ 75.00, $ 150.00 and $ 375.00 for white clover, ryegras and for the chicory - blue grass - red clover mixture being relatively cheap costs to make forage mixtures.